HEIDEGGER’S PHILOSOPHICAL PERSPECTIVE ON TECHNOLOGY ASSISTED HUMAN REPRODUCTION: A CRITICAL EXAMINATION OF TECHNOLOGICAL ENFRAMING ‘GESTELL’ - Yesmin, Sabana; Devi, Sabitri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Traditional ideas and experiences of motherhood are rapidly being erased as a result of the growing acceptance of ARTs, which are changing in previously unheard-of ways how women conceive, gestate, and give birth as well as the cultural connotations traditionally associated with motherhood. Martin Heidegger offered his thoughts on the technological era which may applied in order to explain the increasing use of Assisted Reproductive Technologies (ARTs) in human conception, gestation, and delivery. One of the most important developments in reproductive technology is in vitro fertilization (IVF), which enables people to get over biological constraints by means of technological intervention. Philosophers like Martin Heidegger, however, offer important insights into the ontological and ethical ramifications of IVF that go beyond the medical viewpoint. The criticisms of human autonomy, commercialization, and technology raise significant issues regarding how IVF changes the essence of human reproduction by turning it into a regulated, automated procedure. It applies Heidegger's idea of the technical enframing to modern conceptions of motherhood and human reproduction in a critical and appreciative manner. This paper examine how women's reproductive bodies are revealed as resources in the framed phases of medicalized conception, gestation, and delivery for the mother by applying Heidegger's idea of Gestell(enframing)to the particular context of reproductive enframing.